Adolescência e violência: modos de agir no contemporâneo - Maria do Carmo de Melo Pinheiro (2012)
This dissertation has the propose to discuss violence and aggressive acts via the symptom, in the field Freudian and Lacanian psychoanalyses, listening to what young people try to say precariously through these manifestations. Weve been interested to make an articulation between the ways of acting at the adolescence and the contemporary socio-cultural context, marked by the consumer society, to understand in which way it interferes with the subjectivity of the young, even proposing or yet imposing them a new way of social tie. From this perspective we discuss bullying, nomination that appears trying to capture the structural surplus established by the violence at the otherness field. We found that there is a contemporary attempt of nominate, classify and medicates this surplus, seizing it in the form of evil as an exercise of control over their bodies. We expect so, in an action of rewritten the teenager enjoyment, that implies, on one hand, in his response to not-know to do with the sexual real, and on the other hand the civilization, given the resources he has to repair his symbolic plot weakened. We seek to highlight the importance of the subject to does not go astray of his wish, but (re)invent a new way of dealing with it.